GUIDANCE COUNSELING TEACHERS' EFFORTS TO OVERCOME LATE STUDENTS THROUGH INDIVIDUAL COUNSELING SERVICES AT MTs AL JAM'IYATUL WASHLIYAH TEMBUNG - Sona Satriana; Ali Daud Hasibuan (Conciencia, 2023)
In eradicating tardy behavior and discipline in obeying school rules by students, the role is not only the subject teacher, but the counseling teacher also has a very important role to overcome tardy students. Being late is one of the most commonly seen rule-breaking behaviors in schools. Although being late is not a criminal act against the law like theft and murder, if handling and follow-up efforts are not given, it will have a negative impact on student development, especially in terms of academic achievement. The phenomenon of MTs Al-Jam'iyatul Washliyah Tembung School shows that there are students who are late, the cause of which often occurs due to general factors, family, personal and school factors as a result affecting student learning achievement at school. Qualitative is the method used with a descriptive approach. The BK teacher's effort to resolve late behavior in students is to provide individual counseling guidance services to students. After getting individual counseling guidance services students experience changes in no longer being late for school, their clothes become more rapid and become more quiet.